2023
DOI: 10.1038/s41598-023-45697-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cu/Zn/Iron/Ca/Mg levels and cerebral palsy: a pooled-analysis

Haiquan Zhu,
Song Mao,
Wei Li

Abstract: It was well documented that macro/trace elements were associated with the neurodevelopment. We aimed to investigate the relationship between copper (Cu)/zinc (Zn)/iron/calcium (Ca)/magnesium (Mg) levels and cerebral palsy (CP) by performing a meta-analysis. We searched the PubMed, Embase, Cochrane and Chinese WanFang databases from January 1985 to June 2022 to yield studies that met our predefined criteria. Standard mean differences (SMDs) of Cu/Zn/Iron/Ca/Mg levels between CP cases and healthy controls were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…A CP[23, 28,31,37, 38]. Furthermore, Le Roy et al observed a decline in ferritin levels with increasing age, consistent with the results of our study [28].…”
supporting
confidence: 91%
“…A CP[23, 28,31,37, 38]. Furthermore, Le Roy et al observed a decline in ferritin levels with increasing age, consistent with the results of our study [28].…”
supporting
confidence: 91%